2022
DOI: 10.1002/uog.24844
|View full text |Cite
|
Sign up to set email alerts
|

Early imaging predictors of fetal cerebral ischemic injury in monochorionic twin pregnancy complicated by spontaneous single intrauterine death

Abstract: Objective Monochorionic twin pregnancies are at increased risk of single intrauterine death (sIUD) and subsequent brain injury in the surviving twin owing to shared placentation. We assessed the association between middle cerebral artery peak systolic velocity (MCA‐PSV) and cerebral injury on magnetic resonance imaging (MRI) and examined the association between cerebral findings on diffusion‐weighted imaging (DWI) and those on T2‐weighted imaging following spontaneous sIUD. Methods This was a retrospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
0
14
0
2
Order By: Relevance
“…TTTS cases complicated by severe early onset FGR (and monochorionic twins with severe early onset FGR without TTTS) may be treated with selective fetal reduction to reduce the deleterious effect of in-utero demise on the surviving co-twin. Fetal reduction using either bipolar cord coagulation or radiofrequency ablation has an approximate 15% risk of pregnancy loss, which is less than the 30% risk of adverse outcomes in a surviving co-twin should demise occurs [48][49][50]. Recently, laser ablation of shared placental anastomoses in monochorionic twins complicated by FGR without TTTS has been described.…”
Section: Fetal Growth Restriction Complicating Twin-to-twin Transfusi...mentioning
confidence: 99%
“…TTTS cases complicated by severe early onset FGR (and monochorionic twins with severe early onset FGR without TTTS) may be treated with selective fetal reduction to reduce the deleterious effect of in-utero demise on the surviving co-twin. Fetal reduction using either bipolar cord coagulation or radiofrequency ablation has an approximate 15% risk of pregnancy loss, which is less than the 30% risk of adverse outcomes in a surviving co-twin should demise occurs [48][49][50]. Recently, laser ablation of shared placental anastomoses in monochorionic twins complicated by FGR without TTTS has been described.…”
Section: Fetal Growth Restriction Complicating Twin-to-twin Transfusi...mentioning
confidence: 99%
“…Recent studies have looked at antenatal MRI and its ability to predict a neurological prognosis in the setting of spontaneous sIUFD in MC gestations. One recent retrospective study found that of those with fetal brain MRI for the surviving twin, the rate of abnormal imaging was 34% 42 . Fetuses with severe cerebral injury on MRI following sIUFD were more likely to have an MCA-PSV >1.5MoM (68.8% vs. 38.7); however, a normal MCA-PSV did not rule out neurological injury 42 .…”
Section: Single Intrauterine Fetal Death After First Trimestermentioning
confidence: 99%
“…One recent retrospective study found that of those with fetal brain MRI for the surviving twin, the rate of abnormal imaging was 34% 42 . Fetuses with severe cerebral injury on MRI following sIUFD were more likely to have an MCA-PSV >1.5MoM (68.8% vs. 38.7); however, a normal MCA-PSV did not rule out neurological injury 42 . An elevated MCA alone was found to be poorly predictive of cerebral injury (sensitivity of 68.8% and specificity of 61%) 42 .…”
Section: Single Intrauterine Fetal Death After First Trimestermentioning
confidence: 99%
“…If necessary, magnetic resonance imaging (MRI) should be performed 4 to 6 weeks later after fetal demise. 12,31 However, Shinar et al 49 found that although increased MCA-PSV may be a poor predictor of cerebral injury, early MRI within 2 weeks of sIUD is valuable to identify any cerebral injury with additional diffusion-weighted imaging. Thus, conservative surveillance is suggested when sIUD occurs prematurely, but the utility of MRI with diffusion-weighted imaging to detect brain injury needs more clinical trials.…”
Section: Management Of the Co-twin In Single Intrauterine Demise (Siud)mentioning
confidence: 99%
“…If necessary, magnetic resonance imaging (MRI) should be performed 4 to 6 weeks later after fetal demise 12,31 . However, Shinar et al 49 . found that although increased MCA-PSV may be a poor predictor of cerebral injury, early MRI within 2 weeks of sIUD is valuable to identify any cerebral injury with additional diffusion-weighted imaging.…”
Section: Management Of the Co-twin In Single Intrauterine Demise (Siud)mentioning
confidence: 99%